Ethical opportunities in deep‐sea collection of polymetallic nodules from the Clarion‐Clipperton Zone. (16th December 2021) - Katona, Steven; Paulikas, Daina; Stone, Gregory S.
Abstract: Infrastructure supporting the transition of human societies from fossil fuels to renewable energy will require hundreds of millions of tons of metals. Polymetallic nodules on the abyssal seabed of the Clarion‐Clipperton Zone (CCZ), eastern North Pacific Ocean, could provide them. We focus on ethical considerations and opportunities available to the novel CCZ nodule‐collection industry, integrating robust science with strong pillars of social and environmental responsibility. Ethical considerations include harm to sea life and recovery time, but also the value of human life, indigenous rights, rights of nature, animal rights, intrinsic values, and intangible ecosystem services. A "planetary perspective" considers the biosphere, hydrosphere, and atmosphere, extends beyond mineral extraction to a life‐cycle view of impacts, and includes local, national, and global impacts and stakeholders. Stakeholders include direct nodule‐collection actors, ocean conservationists, companies, communities, interest groups, nations, and citizens globally, plus counterfactual stakeholders involved with or affected by intensification of terrestrial mining if ocean metals are not used. Nodule collection would harm species and portions of ecosystems, but could have lower life‐cycle impacts than terrestrial mining expansion, especially if nodule‐metal producers explicitly design for it and stakeholders hold them accountable. Participants across the value chain can elevate the role of ethics in strategic objective setting, engineering design optimization, commitments to stakeholders, democratization of governance, and fostering of circular economies. The International Seabed Authority is called to establish equitable and transparent distribution of royalties and gains, and continue engaging scientists, economists, and experts from all spheres in optimizing deep‐sea mineral extraction for humans and nature. Nodule collection presents a unique opportunity for an ambitious reset of ecological norms in a nascent industry. Embracing ethical opportunities can set an example for industrial‐scale activities on land and sea, accelerate environmental gains through environmental competition with land ores, and hasten civilization's progress toward a sustainable future. Integr Environ Assess Manag 2022;18:634–654. © 2021 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals LLC on behalf of Society of Environmental Toxicology & Chemistry (SETAC). Key Points: By eliminating emissions from fossil‐fuel combustion, transition to a renewably powered economy is key to mitigating climate change, but there is only a short window, probably less than 10 years, to accomplish it. The renewable transition will require hundreds of millions of tons of new metals, and because demand reduction, recycling, and material substitutions cannot scale quickly enough, meeting that demand will require primary metals from land ores or deep‐sea deposits. Whether or not to use deep‐sea metals has important ethical implications and should not be a yes‐or‐no decision, but instead an inclusive and ethically purposeful effort to weigh scientific information, risks, and benefits associated with the two sources. The overall objective should be policies, decisions, regulations, and agreements that produce the fewest negative impacts on climate, air, water, land, ocean, people, nature, and species, while also providing the most broadly equitable suite of benefits across those categories.